(untitled) (KULT_online, 2009)
Kerstin Hein’s social psychology dissertation joins numerous studies of hybrid identities, but her approach is innovative insofar as it departs from the European context and is based on qualitative interviews with young (German-)Chilean adults who have first-hand experience of emigration. As a result, readers gain insight into possible constructions of hybrid cultural identities. In the course of her study, Hein explores the influence of positive discrimination as well as of colonial and racist discourses within the matrix of migration, culture, and identity. As opposed to using the negatively weighted term "culture conflict", Hein introduces the positive concept of "cultural navigation."